Efektivitas Dan Efisiensi Pemberian Ekstrak Kelenjar Hipofisa Terhadap Pemijahan Ikan Betok (Anabas testudineus Bloch) - - Suriansyah; Muhammad Topan Kamil; Hendri Bugar (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2013)
Extract of the pituitary gland can affect gonadal maturation through control of GnRH and LH release, which hypothalamus releases GtH, and subsequently pituitary gland secretes luteinizing hormone (LH) triggerring steroid hormones on final maturation. The specific objective of this study was to examine the effectiveness and efficiency of the pituitary gland extract for spawning of climbing perch fish. Benefit of this research was as a contribution to the technology development of climbing perch fish hatcheries on peat swamp waters. Usage of pituitary gland extract 0.002 ml/g can speed up the time of ovulation of climbing perch fish 3.77 hours, increase the value of GSI that was 4.72%, and can increase the amount of egg spent on spawning as many as 2915.